PRETEXTS AS THE MOTIVES FOR TRIGGERING ARMED CONFLICTS AND STATES PARTICIPATION - Malendowski, Włodzimierz (Wydawnictwo Naukowe Wydziału Nauk Politycznych i Dziennikarstwa Uniwersytetu im. Adama Mickiewicza w Poznaniu, 2018)
The causes of armed conflicts are a subject of constant interest to the social sciences. This has resulted in many theories and findings regarding the selection of different criteria in determining conflict-triggering factors. In international practice, states decide to declare war citing reasons connected with the state or vital national interests. Sometimes, the true motivations for the use of force are hidden. The history of armed conflicts includes many cases of using contrived pretexts or outright lies to start a war. External circumstances which were beyond the control of the state starting the war and which did not depend on the state’s will and actions have been used as pretexts. Some of the pretexts, however, were deliberately fabricated to justify and explain military operations. States taking advantage of pretexts to use force can be observed from the time of the Trojan War to the attack on Iraq in 2003. Among the countries using pretexts to start a war, the superpowers occupy the leading position – they claim higher purposes, despite the fact that there are no objective criteria upon which to establish their superiority over the conventions of morality and international law.

Przedmiotem stałego zainteresowania nauk społecznych, jest zagadnienie przyczyn konfliktów zbrojnych. Zaowocowało to wieloma teoriami i ustaleniem dotyczącymi doboru różnych kryteriów, w ustalaniu czynników konfliktogennych. W praktyce międzynarodowej państwa decydują się na podjęcie działań wojennych, powołując się na rację stanu lub żywotne interesy narodowe. Niekiedy prawdziwe przyczyny użycia siły są skrywane. Historia konfliktów zbrojnych zna wiele przypadków wykorzystania pretekstów, czyli zmyślonych powodów do rozpoczęcia wojny. Jako pretekst były wykorzystywane obiektywne sytuacje, na które państwo rozpoczynające wojnę nie miały wpływu i nie zależały one od ich woli i poczynań. Natomiast niektóre z pretekstów zostały celowo sfabrykowane, by uzasadnić i usprawiedliwić działania militarne. Takie postępowanie państw, z wykorzystaniem pretekstów do użycia siły, można zaobserwować od czasu wojny trojańskiej, aż do ataku na Irak w 2003 r. W gronie państw korzystających z pretekstów do wszczynania wojny, czołowe miejsce zajmują mocarstwa. Powołują się one przy tym na cele wyższe, mimo że nie ma zobiektywizowanych kryteriów pozwalających ustalić ich wyższość nad normami moralnymi i normami prawa międzynarodowego.
PRETEKSTY – MOTYWEM SPRAWCZYM WYWOŁYWANIA I UDZIAŁU PAŃSTW W KONFLIKTACH ZBROJNYCH
Keywords: pretexts; armed conflicts; states participation; pretekst; konflikty zbrojne; udział państw